Genome-Wide Analysis of Mycoplasma bovirhinis GS01 Reveals Potential Virulence Factors and Phylogenetic Relationships. Issue 5 (1st May 2018) - Chen, Shengli; Hao, Huafang; Zhao, Ping; Liu, Yongsheng; Chu, Yuefeng
Abstract: Mycoplasma bovirhinis is a significant etiology in bovine pneumonia and mastitis, but our knowledge about the genetic and pathogenic mechanisms of M. bovirhinis is very limited. In this study, we sequenced the complete genome of M. bovirhinis strain GS01 isolated from the nasal swab of pneumonic calves in Gansu, China, and we found that its genome forms a 847, 985 bp single circular chromosome with a GC content of 27.57% and with 707 protein-coding genes. The putative virulence determinants of M. bovirhinis were then analyzed. Results showed that three genomic islands and 16 putative virulence genes, including one adhesion gene enolase, seven surface lipoproteins, proteins involved in glycerol metabolism, and cation transporters, might be potential virulence factors. Glycerol and pyruvate metabolic pathways were defective. Comparative analysis revealed remarkable genome variations between GS01 and a recently reported HAZ141_2 strain, and extremely low homology with others mycoplasma species. Phylogenetic analysis demonstrated that M. bovirhinis was most genetically close to M. canis, distant from other bovine Mycoplasma species. Genomic dissection may provide useful information on the pathogenic mechanisms and genetics of M. bovirhinis .